Promoting electrocatalytic CO2 reduction to formate via sulfur-boosting water activation on indium surfaces - Ma, Wenchao; Xie, Shunji; Zhang, Xia-Guang; Sun, Fanfei; Kang, Jincan; Jiang, Zheng; Zhang, Qinghong; Wu, De-Yin; Wang, Ye (Nature communications, 2019)
Electrocatalytic reduction of CO 2 to fuels and chemicals is one of the most attractive routes for CO 2 utilization. Current catalysts suffer from low faradaic efficiency of a CO 2 -reduction product at high current density (or reaction rate). Here, we report that a sulfur-doped indium catalyst exhibits high faradaic efficiency of formate (>85%) in a broad range of current density (25–100 mA cm −2 ) for electrocatalytic CO 2 reduction in aqueous media. The formation rate of formate reaches 1449 μmol h −1 cm −2 with 93% faradaic efficiency, the highest value reported to date. Our studies suggest that sulfur accelerates CO 2 reduction by a unique mechanism. Sulfur enhances the activation of water, forming hydrogen species that can readily react with CO 2 to produce formate. The promoting effect of chalcogen modifiers can be extended to other metal catalysts. This work offers a simple and useful strategy for designing both active and selective electrocatalysts for CO 2 reduction. CO 2 conversion to liquid fuels provides an appealing means to remove the greenhouse gas, although it is challenging to find materials that are both active and selective. Here, authors show sulfur-doped indium to be a highly active and selective electrocatalyst that transforms CO 2 into formate.